The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1088/1742-6596/956/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity optimization in whispering gallery mode optical cylindrical biosensors

Abstract: Abstract. Whispering-gallery-mode resonances propagated in cylindrical resonators have two angular and radial orders of l and i. In this work, the higher radial order whispering-gallerymode resonances, (i = 1 − 4), at a fixed l are examined. The sensitivity of theses resonances is analysed as a function of the structural parameters of the cylindrical resonator like different radii and refractive index of composed material of the resonator. A practical application where cylindrical resonators are used for the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In this scheme of detection, the bio/chemical analytes are directly detected without the laborious process of analyte molecule labeling [ 10 , 11 , 12 ]. Regarding their transducer part, optical biosensors are categorized into different groups of resonator-based [ 13 , 14 , 15 ], waveguide-based [ 16 , 17 ], and interferometric-devices based [ 18 , 19 ]. Although these optical sensors have demonstrated high sensitivities for both bulk and surface sensing measurements [ 20 , 21 , 22 ], they still suffer from a critical issue.…”
Section: Introductionmentioning
confidence: 99%
“…In this scheme of detection, the bio/chemical analytes are directly detected without the laborious process of analyte molecule labeling [ 10 , 11 , 12 ]. Regarding their transducer part, optical biosensors are categorized into different groups of resonator-based [ 13 , 14 , 15 ], waveguide-based [ 16 , 17 ], and interferometric-devices based [ 18 , 19 ]. Although these optical sensors have demonstrated high sensitivities for both bulk and surface sensing measurements [ 20 , 21 , 22 ], they still suffer from a critical issue.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that whispering gallery mode (WGM) resonators like ring resonators can be used as label-free biosensors [10][11][12]. Other geometries of WGM-resonator-based biosensors, like spherical [13,14], cylindrical [15][16][17], and disk structures [18,19], have emerged as alternative device geometries in biosensing. While WGM microsphere and microcylinder biosensors exhibit high quality factors, their circuit integration, mass production and reproducibility are extremely challenging [13].…”
Section: Introductionmentioning
confidence: 99%
“…In our previously published works, we have presented a simple analytical method for modelling of cylindrical resonator based biosensors [16,17]. Here, we use some fast analytical methods to analyze a SOI WGM ring resonator coupled to a straight waveguide.…”
Section: Introductionmentioning
confidence: 99%